Cloud computing : 5th International Conference, CloudComp 2014, Guilin, China, October 19-21, 2014, Revised selected papers /: 5th International Conference, CloudComp 2014, Guilin, China, October 19-21, 2014, Revised selected papers. (2015) - Unknown
No abstract available